Effect of the type of pruning in the phenology of the custard apple (annona cherimola M.) In agro-ecological conditions of Cayhuayna - Vidal Jaimes, Edwin Rubén (2017)
The research work conducted in permanent plantations of the custard apple tree of the fruit ResearchInstitute Olericola of the Faculty of Agricultural Sciences, located at 1 948 masl, it was conductedwith the objective of determining the effect of the type of pruning, in the phenology of the custardapple. The sample of 144 plants were distributed in three treatments were rejuvenation pruning,fruiting, and mixed with three repetitions in complete design at Random. It was concluded thatthe types of pruning have no effect in time of latency, sprouting and emission of leaves. Trees withpruning of rejuvenation showed precocity to differentiate buds in nine days; 93,3% of flourishingwith normal petals and 66,7% of fruiting. The types of pruning has no significant effect in numberof buds for meristem, number of leaves in branches of determined and undetermined growth, nor innumber of active meristems; but if for number of latent and total meristemos. The fruiting pruningpresented less quantity of latent meristems (1,77) and the pruning of rejuvenation has the highestnumber of meristems per stump (10,0). The type of pruning influences the increase in the size andwidth of leaves, corresponding to rejuvenation pruning (18,56 cm x 12,32 cm) and fruiting (17,27cm x 12,26 cm); the mixed pruning put forward the smaller size and width of leaf blade (15,62 cmx 10,19 cm).